Religiusitas, Kepercayaan pada Aparat, Tingkat Pendidikan, Pengetahuan Perpajakan dan Kepatuhan Wajib Pajak - Octavianny, Priscilla; Makaryanawati, Makaryanawati; Edwy, Ferby Mutia (E-Jurnal Akuntansi, 2021)
The purpose of this study is to determine the effect of religiosity, trust in the apparatus, education level and tax knowledge on Non-Employee Individual Taxpayer compliance. This research was conducted at KPP Pratama, South Malang. The number of samples in this study were 100 respondents with a sampling method using accidental sampling method. Data collection is done through questionnaires. The   data analysis technique used in this research is multiple linear regression. Based on the results of the analysis it can be seen that religiosity, trust in the apparatus, education level and tax knowledge have a positive effect on tax compliance. Keywords: Tax Compliance; Religiosity, Trust in The Apparatus; Education Level; Tax Knowledge.